Eksplorasi Spiritualitas Batak terhadap Generasi Muda di Era Digital dalam Pendekatan Budaya - Gultom, Yosua Xpistos (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2025)
Batak spirituality in the digital era is undergoing significant challenges and transformations in meaning, especially among the younger generation. This spirituality is deeply rooted in belief in God, reverence for ancestors, and harmony with nature. This study aims to explore how young people understand and implement Batak spirituality within the context of digital culture, as well as how these transformations affect the sustainability of cultural values. The research employs a qualitative approach with observation and in-depth interviews involving ten informants representing Generations Z, X, and Baby Boomers. Data were analyzed thematically to identify patterns in the intergenerational interpretation of spirituality. The findings reveal that younger generations tend to integrate Batak spiritual values into Christian religiosity while maintaining cultural symbols as a form of identity. The digital era offers new opportunities for preserving spiritual values, but it also poses risks of symbolic dilution and loss of context. Thus, Batak spirituality today does not disappear but adapts in form to remain relevant in contemporary life.